Identifikasi Masjid Lautze 2 Bandung: Transformasi Ruang Dari Fungsi Komersial Menjadi Fungsi Peribadatan - Putri Setiawan, Nurfitria; Astrid Hertoety, Dianna; Rachmawan Sukardi, Rahy; Maulana Subki, Raksa; Arvina Yusuf, Stephanie (CV RIFAINSTITUT, 2025)
The transformation of commercial spaces into places of worship reflects the evolving spatial needs of urban communities, particularly in response to the growing population of Muslim converts (mualaf). Masjid Lautze 2 in the Tamblong area of Bandung stands as a distinctive example of such a transformation, where a shop-house (ruko) was adapted to serve religious purposes. Despite its relevance, academic studies examining changes in spatial function and architectural elements in commercial buildings converted into mosques remain limited. This study aims to identify the shift from commercial to religious function and to examine which architectural elements have been preserved after the transformation. A qualitative approach with a descriptive-analytic method was employed, involving site surveys, interviews, and photographic documentation as the basis for analysis. The findings indicate that significant spatial changes occurred on the ground floor, where commercial functions were replaced with religious facilities, including separate prayer areas for men and women, a mihrab, ablution areas, restrooms, an administrative room, a storage area, and an internal staircase. In contrast, the upper floor retained its original residential function. From an architectural standpoint, key structural elements such as original walls, columns, and beams—especially on the building’s exterior and in the upper-floor interiors—were preserved. These findings highlight how spatial transformation can accommodate new functional demands while maintaining the architectural identity of the original structure.